PERFIS DE ERIC-PCR DE Escherichia coli E E. coli O157:H7 EM MEIAS-CARCAÇAS BOVINAS - COSTA, Joice Vinhal (2008)
There are different sorotypes of Escherichia coli responsable for enteric disfunctions, and in the most of time those are related with meat consume or contaminated food that had not been cooked with an efficient thermal treatment before been ingested. In Brazil there aren t inform data of possible outbreaks caused by E. coli O157:H7, but this pathogen has been frequently isolated from cattle s feces, and it was recently isolated from bovine carcass at two slaughterhouses in Goiás. The present study has the objective to characterize by ERIC-PCR E. coli and E. coli O157:H7 detected at bovine carcass surfaces and check the power of this methodology to identify different isolates of E. coli and E. coli O157:H7. ERIC-PCR was used to characterize 111 samples, and it was obtained 32 fingerprints separated in 90 isolates of E. coli and eight fingerprints separated in 16 isolates of E. coli O157:H7. From the total of 111 samples, two isolates of E. coli and five of E. coli O157:H7 were non-tipables. The fingerprints varies from one to 18 bands. The discrimination between the samples was high, showing the big power of ERIC-PCR to discriminate isolates from one specie. The discriminatory index between E. coli and E. coli O157:H7 obtained was 0,96.